Der Staat als Zuhälter Die Abschaffung der reglementierten Prostitution in Deutschland, Frankreich und Italien im 20. Jahrhundert - König, Malte (Bibliothek des Deutschen Historischen Instituts in Rom, 2016)
Until the 20th century there were brothels throughout Europe where prostitution was controlled by the state. The study examines factors in the German, French, and Italian parliaments that gave impetus to the abolition of this system. Besides hygienic, moral, and human rights concerns, the discussion also involved questions of security and foreign policy.